Morphophysiology of caetê plants under sun exposure and soil textures - Barbosa, Jaqueline Araujo; Ferreira, Silvio Douglas; Brito, Tauane Santos; Guimarães, Vandeir Francisco; Costa , Neumarcio Vilanova da (Scientia Agraria Paranaensis, 2022)
Easily found in humid and shady places, Maranta sobolifera has spread in agricultural areas. However, the lack of information on the development of the species in different environments makes it difficult to understand its adaptive capacity. This paper evaluated the morphophysiological changes of M. sobolifera plants to sun exposure and soil textures. In a completely randomized experimental design and split plots, the main plots corresponded to light exposure and the subplots to soil textures. Gas exchange indices, stomatal density, chlorophyll a, b and total contents, macronutrients and dry mass were evaluated. The lower incidence of luminosity increases the photosynthetic rate by an average of 43% and 33% in clayey and sandy soils, respectively. Stomatal density was higher in full sun, while chlorophyll contents a and b were higher in shaded plants. The N and K contents in leaves, stems and roots were higher in shaded plants by up to 37%. The P content in the stem was 69% and 48% higher in plants grown in clayey and sandy soil, respectively. Dry mass was 26% higher in shaded plants compared to plants grown in full sun. In clayey soil, the total dry mass was 42% higher in relation to plants in sandy textured soil. It is concluded that M. sobolifera plants show morphophysiological changes (>stomatal density) that help adapt to full sun. However, under the canopy of agricultural crops, this species can compete intensely for nutrients, especially in clayey soils.